Trends in utilization of imaging among ophthalmic-related emergency department visits in the United States - Chou, Brandon; Shah, Serena M.; Kalavar, Meghana; Sridhar, Jayanth; MacIntosh, Peter; Lee, Andrew G. (Frontiers in Ophthalmology, 2026)
BackgroundAdvanced neuroimaging use has increased in U.S. emergency departments (EDs), including for neuro-ophthalmic conditions requiring computed tomography (CT) or magnetic resonance imaging (MRI) and their use has shifted in recent years amid changing care patterns and the COVID-19 pandemic. To evaluate these changes, this study examined national trends of CT and MRI use for eye-related ED visits from 2016 to 2022.Materials and methodsA retrospective trend study was conducted using 2016–2022 National Hospital Ambulatory Medical Care Survey (NHAMCS) data. Eye-related ED visits involving CT or MRI were identified using standardized diagnostic and procedure codes. Weighted national estimates were calculated, trends were assessed with Joinpoint regression to estimate average annual percent change (AAPC), and multivariable logistic regression identified patient- and hospital-level factors associated with imaging.ResultsFrom 2016 to 2022, eye-related ED visits totaled 42,151,975, involving 15,580,699 advanced imaging studies. Although the number of visits involving imaging remained stable, increasing by 0.8% [2,545,867 in 2016 to 2,566,826 in 2022; Average Annual Percent Change (AAPC): -0.1%], imaging rates per 1,000 visits climbed by 21.8% (AAPC: 3.1%). CT usage declined (2,445,326 in 2016 to 2,412,225 in 2022; AAPC: -1.3%), while MRI usage rose (332,588 in 2016 to 345,153 in 2022; AAPC: 1.0%). Younger age, race (particularly black patients), and Medicaid coverage were associated with reduced likelihood of imaging, while residence in the Midwest or South increased odds. Hospital admission remained the strongest predictor, tripling the likelihood of imaging. The COVID-19 pandemic drove a notable rise in imaging rates (from 34.9% before the pandemic to 40.1%; p=0.003).ConclusionAdvanced imaging use during eye-related ED visits increased from 2016 to 2022 with a shift toward greater MRI utilization and stable CT usage. Demographic factors and the COVID-19 pandemic potentially contributed to these trends and observed racial disparities highlight potential systemic barriers to imaging access. Despite limitations related to hospital representation and data scope, these findings emphasize the need for further research to explore drivers of imaging use and address healthcare inequities.